Training Seminar on Domestic Violence and Child Abuse - Part 20/24
In September 2000, three programs of the Open Society Institute-Budapest (Network Women’s Program, Network Child Abuse Treatment and Prevention Program, and Network Media Program) hosted the double training for representatives of Eastern Europe and the post-Soviet countries in Budapest, focusing on the issues of family violence and child abuse. Title of Seminar: In Our Best Interest: Facilitating Groups for Abused Women (Court Room) Date: 05.09.2000.